Teaching Arabic From Behavioral Learning Theory (Ivan Petrovich Pavlov) By Drill And Practice Technology In The Mambaul Hikam One Islamic High School Lumajang For The Academic Year 2020/2021: تعليم اللغة العربية من نظرية التعلم السلوكية ايفان بتروفيتش بافلوف (Ivan Petrovich Pavlov) بتقنية Drill و Practiceفي المدرسة الثانوية الإسلامية منبع الحكم الواحدة لوماجانج للسنة الدراسية 2020/2021م - Elis Safitri (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2021)
Analysis of Arabic learning in terms of Ivan Petrovich Pavlov's behavioristic learning theory with drill and practice techniques written by Elis Safitri discusses how to the Arabic language learning process takes place using drill and practice techniques in terms 0f Ivan Pavlov's behavoristic learning theory and what factors influence it in his learning. This study uses a qualitative field research method. The result of this research is the implementation of Arabic language learning through 3 stages : planning, implemention and evaluation. In the implemention of learning in accordance with the application of Ivan Pavlov's behavioristic learning theory, where the teacher gives an example first and then the students follow it. And several factors that affect the implemention of learning, there are advantages and disadvantages. As for one of the advantages, the orientation of student learning lies in the results. And the disadvantages is that students only focus on result and only always follow the teacher without any creativity.